Determinants of Consumer Purchase Interest Factors for Immune-enhancing Herb Products During Covid 19 Pandemic - Evi Sofiana (Politeknik Negeri Bengkalis, 2021)
Currently, almost all countries including Indonesia are experiencing the Covid 19 pandemic and until now the vaccine has not been given to prevent the disease. One of the ways that people recommend doing is having a healthy lifestyle in order to increase body immunity. During this pandemic, the demand for herbal products has increased along with the public's awareness to maintain endurance in facing the corona outbreak.The purposes of this study was to empirically examine the effect of product quality, price, subjective norms and consumers’ buying interest towards immune-enhancing herbal products during the Covid 19 pandemic and to see which factors had influenced the most. The research method used is a survey using a questionnaire as a data collection tool. The samples were selected by non probability sampling method, namely convenience sampling of 100 respondents.Based on the hypotheses test results, it is proven that there is a significant and positive influence between product quality and consumers’ buying interest on herbal products with CR=2,696, there is a significant and positive influence between product prices and consumers’ buying interest on herbal products with CR=4.139 , there is a significant and positive influence between subjective norms and consumer buying interest in herbal products with CR=5,128 and there is a significant and positive influence between trust and consumer buying interest on herbal products to increase immunity during the Covid 19 pandemic with CR=5.792The determinants of consumers’ buying interest on herbal products to increase immunity during the Covid 19 pandemic are trust, subjective norms, product prices and product quality, respectively.